PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN PERUSAHAAN - Rosmida Rosmida; Nurhazana Nurhazana (Politeknik Negeri Bengkalis, 2015)
Abstract:This study examines the impact of audit committee characteristics on the level of voluntary disclosure in the annual reports of listed Indonesian firms. Audit committee characteristics are: financial expert, meeting number, and diligence. Content analysis is used to collect the required data from the2013 annual reports of 201 non-finance firms listed on the Indonesia Stock Exchange.The method of data analysis is multiple regression. This study employs agency theory as underlying theory. The results show that audit committee characteristicshave insignificant effect on the level of voluntary disclosure in the annual reports. Voluntary disclosure, financial expert, meeting, diligence.